Intermediate-scale investigation of nonaqueous-phase liquid architecture on partitioning tracer test performance - Elena Moreno-Barbero (2018)
Partitioning interwell tracer tests (PITTs) have been proposed as a tool to characterize source zones of waste sites with chemicals entrapped in the form of nonaqueous-phase liquids (NAPLs). This technique has the potential to be applied to NAPL source characterization of both the vadose and saturated zones, but the recent applications have been primarily focused on dense NAPLs (DNAPLs) entrapped below the water table. This study presents an intermediate-scale experiment to investigate the applicability of the technique to heterogeneous sites with complex NAPL entrapment architecture. Tracer experiments were conducted in an intermediate-scale test tank (4.87 by 1.21 by 0.05 m) with heterogeneity defined using the geostatistical parameters of a spatially correlated random field. Tetrachloroethene (PCE), a DNAPL, was spilled into the heterogeneous packing and was allowed to distribute naturally, creating zones of both residual and pooled entrapment. The saturation distribution of the DNAPL was determined in situ using a gamma attenuation system. Once the saturation distribution was characterized, a set of tracer tests was conducted. Results of this study demonstrate how the inversion of the tracer breakthrough concentrations provided valuable information to establish the validity of the use of equilibrium partition coefficients in situations where tracer partitioning might be controlled by nonequilibrium behavior. While our previous work quantified the estimation error introduced by the assumption of equilibrium partitioning in tracer data analysis, this study demonstrated that more accurate NAPL estimates can be obtained using effective partition coefficients in combination with inverse modeling methods upscaled for more realistic heterogeneous settings. © Soil Science Society of America. All rights reserved.